Two light-transducing membrane proteins: bacteriorhodopsin and the mammalian rhodopsin. - Khorana, H G (1993)
Site-directed mutagenesis has provided insight into the mechanisms of action of bacteriorhodopsin and rhodopsin. These studies are summarized here.